-3.6c-3.49=-5.14+5.9-3.1c

Simple and best practice solution for -3.6c-3.49=-5.14+5.9-3.1c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3.6c-3.49=-5.14+5.9-3.1c equation:



-3.6c-3.49=-5.14+5.9-3.1c
We move all terms to the left:
-3.6c-3.49-(-5.14+5.9-3.1c)=0
We add all the numbers together, and all the variables
-3.6c-(-3.1c+0.76)-3.49=0
We get rid of parentheses
-3.6c+3.1c-0.76-3.49=0
We add all the numbers together, and all the variables
-0.5c-4.25=0
We move all terms containing c to the left, all other terms to the right
-0.5c=4.25
c=4.25/-0.5
c=-8+0.25/0.5

See similar equations:

| 5x-9=6x+23 | | 100=2t+22 | | -9b+10=-10-4b-10 | | x-21/5x=3 | | 4)4(-1+m)=-56 | | (x+9)*9=15^2 | | -5g-10=3+3-g | | 3x+4x+5=2x+7 | | p+(-24)=-18 | | 18s+3/4=336 | | 1-3h+9=10-h | | 2(x-4)+8x=30 | | -5x-11=14= | | 13x+45=19x+3+6x+2+12x-4=180 | | 5(k-85)=50 | | 18s+¾=336 | | 63.13=10.7x | | -y-8-2y=7y-8 | | 0.35(x+4)=(x-6) | | 0=18+6(m-1) | | 3(5b+2)=b+6 | | 2x^2−50=150 | | 6y=3y-45 | | 1/3(3x-12=-17 | | 2+7b=-2+8b | | 2/5=v-2 | | 2(y+3)=12+4 | | 3x=361 | | 17d+2-d=18 | | 10s+1=-7-s+9s | | 4x+18+2x=6(x+3) | | 8-4x=2(x-2 |

Equations solver categories